2016
DOI: 10.1111/joim.12491
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D insufficiency and cognitive impairment in Asians: a multi‐ethnic population‐based study and meta‐analysis

Abstract: Vitamin D insufficiency is associated with a greater likelihood of and more severe cognitive impairment in Asian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…There have also been data showing vitamin D deficiency to be associated with cardiovascular disease [7], cancer [7], diabetes [8], cognitive impairment [9], and all-cause mortality [10], although evidence for these non-skeletal conditions remain inconclusive [11]. These detrimental effects are not limited to persons with deficient vitamin D levels, as a systematic review found that merely having an insufficient 25(OH)D concentration (21–29 ng/mL [12]) predisposed women to breast cancer, and poorer survival rates in those diagnosed with lymphoma [13].…”
Section: Introductionmentioning
confidence: 99%
“…There have also been data showing vitamin D deficiency to be associated with cardiovascular disease [7], cancer [7], diabetes [8], cognitive impairment [9], and all-cause mortality [10], although evidence for these non-skeletal conditions remain inconclusive [11]. These detrimental effects are not limited to persons with deficient vitamin D levels, as a systematic review found that merely having an insufficient 25(OH)D concentration (21–29 ng/mL [12]) predisposed women to breast cancer, and poorer survival rates in those diagnosed with lymphoma [13].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D can play an important role in brain health and function, and exert various neuroprotective effects in brain areas essential for cognition 6. Being severely deficient in vitamin D is associated with a more than twofold increased risk of developing dementia 7.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that vitamin D receptors are widespread in both neurons and glial cells. [3][4][5] Animal experiments based on mice have also demonstrated that vitamin D deficiency leads to mild cognitive impairment. 2 Therefore, vitamin D may be related to cognition.…”
Section: Introductionmentioning
confidence: 99%